Termodinamske in transportne lastnosti sistemov polimerov in biološko aktivnih spojin s superkritičnimi fluidi - Trupej, Nina (visokošolska dela, 2016)
Due to the growing tendency to develop green technologies which are not harmful to the environment, and methods of processing the material, which do not contain traces of toxic organic solvents, such as has been the usual practice in conventional processes, we have focused on supercritical fluids, which are increasingly recognized in the industry. The doctoral dissertation contains data on phase equilibria and solubility needed for the design of high-pressure processes that use supercritical fluids. We have studied systems of polyethylene glycol (PEG) with molar masses 1 500 g/mol, 4 000 g/mol, 10 000 g/mol, 35 000 g/mol and fluids argon, propane and sulfurhexafluoride (SF6), vitamin K3/carbon dioxide and naphthol/carbon dioxide. On the basis of experiments for the systems PEG/fluid, we found that various fluids (CO2, propane, SF6, argon) have various thermodynamic and transport properties in the binary system. We did an extensive study examining the solubility, diffusion coefficent, melting point, desorption time, etc. Each fluid has, due to its unique properties, different impact on the binary system PEG/fluid and on properties such as melting point, solubility and diffusion coefficient, and we can obtain products with different characteristics. These data were examined for planning the micronization process of PEG with PGSS (Particles from Gas Saturated Solutions). It has been found that PEG can be micronised with the fluids propane, SF6 and argon at a lower pressure than that with CO2. PEG micronization was performed at the conditions of melting point minimum under pressure of fluid and at 328 K and 15 MPa. In addition, we obtained particles which are more uniform in size and have more spherical shapes as with the micronization with CO2. Such manufactured particles with uniform shapes and sizes, are attractive for producers of solids, powdery products, since they are of higher quality. The system of vitamin K3/CO2 was studied at temperatures of 313 K, 333 K and 353 K and pressures up to 40 MPa, and compared with literature. The results show that the solubility of the vitamin K3 differ from the data in the literature, which was attributed to the use of different methods of equilibrium establishemnt, sampling and analysis. We have determined the partial molar volumes, which are markedly large and negative before and near of the critical point, which indicates strong interactions between the molecules of the solvent and solute. With the determination of the partial molar volumes, the occurrence of the maximum solubility can be predicted, which, in the case of the solubility of vitamin K3 in the CO2, occurs at a temperature of 313 K and 333 K. In the case of determining the density of a binary system of vitamin K3/CO2, we have found that models based on the density of the binary system, have to take into account the differences between the densities of the binary system and the densities of pure fluids that occur below the critical point. The difference between the density of the binary system of vitamin K3/CO2 and pure CO2 fluid can be even 100% or more. Melting point of naphthol under pressure of CO2 has a temperature minimum at pressure 20 MPa. The solubilities of 1-naphthol in CO2 at temperatures of 313 K, 333 K and 353 K, are higher than the solubility of 2-naphthol in CO2. The solubilities presented in this work are higher for two orders of magnitude compared to literature. The densities of the system naphthol/CO2 at conditions below the critical point are much higher than the density of pure CO2 and at higher pressures, the density of the binary system can be lower than the density of pure CO2.
Keywords: density; gostota; naftol; naphtol; PGSS; polietilen glikol; polyethylene glycol; solubility; supercritical fluids; superkritični fluidi; topnost; vitamin K3